POLYSACCHARIDE BASED CONTROLLED RELEASE MUCOADHESIVE DRUG DELIVERY SYSTEM FOR PAIN MANAGEMENT (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Mucoadhesion is one of the most extensively studied methods for the administration of medication for faster onset of action with enhanced bioavailability. Present investigation was concerned with the development and characterization of controlled release muco-adhesive drug delivery system for the drug Tramadol Hydrochloride (TRD) to extend the duration of analgesia for patients suffering from acute to chronic pain. Formulations were made using the solvent casting technique, incorporating natural polymers like Guar Gum, Xanthum Gum and Chitosan in conjunction with HPMC (hydroxy propyl methyl cellulose) to modify the drug release. The compatibility of film components were validated by Fourier Transform Infra- Red (FTIR) spectroscopy and subjected to physico-chemical evaluation parameters and ex-vivo drug diffusion study. Optimized formulation was tested for analgesic efficacy in vivo to determine extent of their suitability in therapeutic use. All the prepared formulations exhibited superior pharmaceutical qualities with respect to drug content, folding endurance, swelling index and mucoadhesion time. In ex-vivo drug diffusion study, all the films displayed a controlled release lasting longer than eight hours. Formulations containing Chitosan in combination with HPMC (F6) showed better controlled drug release over other combinations. The formulation F6 bring out remarkable in vivo analgesic efficacy with 58.10 % analgesia in contrast to the standard (61.16%). It was deduced that Tramadol hydrochloride mucoadhesive films were found to be an effective treatment for moderate to severe pain with a quick onset and a lengthy half-life.